Changes of bone turnover markers and serum PTH after night or morning administration of zoledronic acid in breast cancer patients with bone metastases. - Generali, D; Dovio, A; Tampellini, M; Tucci, M; Tedoldi, S; Torta, M; Bonardi, S; Allevi, G; Aguggini, S; Milani, M; Harris, A; Bottini, A; et al. (2008)
Persistent circadian rhythm of bone turnover in bone metastatic breast cancer suggests greater skeletal retention of bisphosphonates if administered in the night. We assessed differential effects of night vs morning administration of zoledronic acid (ZA) on bone turnover. Forty-four breast cancer patients with bone metastases were randomised to receive intravenous ZA (4 mg) at 1100 or 2300 hours every 28 days for four times. Urinary concentration N-telopeptide of type-I collagen (NTX) and deoxypyridinolines, and serum C-telopeptide of type-I collagen (CTX), bone alkaline phosphatase (ALP), osteocalcin and Parathyroid hormone (PTH) was measured in the morning at baseline and after 4, 7, 14, 28, 56 and 84 days. Urinary ZA concentration was also measured. Zoledronic acid caused significant decreases of NTX and CTX (P<0.001), without any difference in percent changes between night and morning arms. Bone ALP and osteocalcin were also significantly affected by ZA (P=0.001), without any difference between arms. Parathyroid hormone significantly increased in both the arms; PTH increase was lower in the night arm (P=0.001). From the second administration onwards, urinary ZA level was significantly higher in the night arm (P<0.01). Administration of ZA at two opposite phases of the circadian cycle causes similar changes of bone-turnover marker levels, but has differential effects on the level of serum PTH.